Invasive Mold Infections: Virulence and Pathogenesis of Mucorales. (1st November 2011) - Morace, Giulia; Borghi, Elisa
Abstract : Mucorales have been increasingly reported as cause of invasive fungal infections in immunocompromised subjects, particularly in patients with haematological malignancies or uncontrolled diabetes mellitus and in those under deferoxamine treatment or undergoing dialysis. The disease often leads to a fatal outcome, but the pathogenesis of the infection is still poorly understood as well as the role of specific virulence determinants and the interaction with the host immune system. Members of the order Mucorales are responsible of almost all cases of invasive mucormycoses, the majority of the etiological agents belonging to the Mucoraceae family. Mucorales are able to produce various proteins and metabolic products toxic to animals and humans, but the pathogenic role of these potential virulence factors is unknown. The availability of free iron in plasma and tissues is believed to be crucial for the pathogenesis of these mycoses. Vascular invasion and neurotropism are considered common pathogenic features of invasive mucormycoses.